Are Randomness of Behavior and Information Flow Important to Opinion Forming in Organization? - Agnieszka KOWALSKA-STYCZEN; Krzysztof Malarz (Communications of International Proceedings, 2020)
We examine how the randomness of behavior and the flow of information between agents affect the formation of opinions. Our main research involves the process of opinion evolution, opinion clusters formation and studying the probability of sustaining opinion. The results show that opinion formation (clustering of opinion) is influenced by both flow of information between agents (interactions outside the closest neighbors) and randomness in adopting opinions.
Keywords: Opinion Dynamics; Social Modelling; Organization; Social Complex System; Agent-Based Model